Functional Outcomes of 24-Hour Thumb Immobilization in Healthy Volunteers: Prospective Comparative Study - Muppavarapu, Raghuveer C.; Tsytsikova, Lyubov; Gottschalk, Michael B.; Dalwadi, Poonam P.; Cassidy, Charles (Journal of Wrist Surgery, 2017)
Background Immobilization is often needed for the treatment of wrist and hand injuries. The current best method of immobilization for several types of injuries has yet to be elucidated with little being reported on the functional differences of each type of immobilization.Purpose The purpose of this study is to compare the functional outcome between healthy young volunteers with a 24-hour short arm cast (SAC) versus thumb spica cast (TSC) immobilization.Methods A total of 50 healthy volunteers completed a baseline typing assessment and a Patient-Reported Outcomes Measurement Information System (PROMIS) upper extremity functional scoring assessment. Participants in group 1 were randomly initially assigned to a TSC of their dominant hand followed by an SAC, whereas participants in group 2 were randomly initially assigned to a TSC of their nondominant hand followed by an SAC. The volunteers completed the typing assessment and PROMIS assessment at the end of the 24-hour casting period.Results A total of 50 participants were enrolled in the study with 25 in group 1 and 25 in group 2. There was a 24.3-point difference between the average PROMIS score for participants with SAC compared with participants with TSC (93 vs. 68.7; p = 0.0001). There was a significant difference between the typing speed and accuracy of participants with SAC compared with participants with TSC (p = 0.0001).Conclusion There is a significant difference in functionality of a TSC immobilization versus an SAC immobilization according to the PROMIS functional outcome score and typing speed in a 24-hour casting period. SAC immobilization should be considered to have a possible similar effect in pathologic conditions instead of TSC immobilization given these findings even though a 24-hour period is not enough to provide adequate long-term conclusions.Level of Evidence I, prospective comparative study.
Keywords: cast immobilization; short arm cast; thumb spica cast; wrist immobilization